The relationship between mental disorders and use of psychoactive substances in Medical students: an integrative review (Research, Society and Development, 2022)
Recent studies correlate the abusive use of these substances with the development or aggravation of mental disorders and the literature demonstrates a high prevalence of drug use among medical students, in this way the analysis of the factors associated with the precariousness of the mental health of academics from medicine and the association with the abuse of licit and illicit substances is demonstrated as an urgency of public and educational health. This study identify the evidence and address the issue of the relationship between mental disorders and the use of psychoactive substances by medical students. This is an integrative review of the scientific literature from publications from 2017 to 2022. The databases SciELO, PUBMED, UpToDate, Lilacs and Google Scholar were chosen, using search terms identified in the Health Sciences Descriptors (DeCS) in Portuguese, English and Spanish. As for the methodology, it is an integrative literature review, where a critical analysis of the studies presented, discussion of the results and after that the presentation of the integrative literature review based on the authors' interpretation, based on selected articles. In conclusion, it was observed that the use of psychoactive substances can exacerbate mental disorders in medical students, since they do not treat the cause, they only change the symptoms in a momentary way, often being able to change the brain chemistry, resulting in health damages.